Reciprocal Substitution Between Methamphetamine and Heroin in Terms of Reinforcement Effects in Rats - Mei, Di-sen; Cai, Yu-jia; Wang, Fang-min; Ma, Bao-miao; Liu, Hui-fen; Zhou, Wen-hua; Xu, Jiang-ping (Frontiers in Psychiatry, 2020)
Heroin and methamphetamine are both popular illicit drugs in China. Previous clinical data showed that habitual users of either heroin or methamphetamine abuse the other drug for substitution in case of unavailability of their preferred drug. The present study aimed to observe whether heroin can substitute the methamphetamine reinforcement effect in rats, and vice versa. Rats were trained to self-administer heroin or methamphetamine (both 50 μg/kg/infusion) under an FR1 reinforcing schedule for 10 days. After having extracted the dose–effect curve of the two drugs, we administered methamphetamine at different doses (12.5–200 μg/kg/infusion) to replace heroin during the period of self-administration, and vice versa. The heroin dose–effect curve showed an inverted U-shaped trend, and the total intake dose of heroin significantly increased when the training dose increased from 50 to 100 or 200 μg/kg/infusion. Following replacement with methamphetamine, the total dose–effect curve shifted leftwards and upwards. By contrast, although the dose–effect curve of methamphetamine also showed an inverted U-shaped trend, the total dose of methamphetamine significantly decreased when the training dose decreased from 50 to 25 μg/kg/infusion; conversely, when the methamphetamine training dose increased, the total dose did not change significantly. The total dose–effect curve shifted rightwards after heroin was substituted with methamphetamine. Although heroin and methamphetamine had their own independent reward effects, low doses of methamphetamine can replace the heroin reward effect, while high doses of heroin can replace the methamphetamine reward effect. These results demonstrated that heroin and methamphetamine can substitute each other in terms of reinforcement effects in rats.